2021
DOI: 10.3389/fpls.2021.696955
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Cuticle Functionality and Robust Resistance to Botrytis cinerea in Arabidopsis thaliana Plants With Altered Homogalacturonan Integrity Are Dependent on the Class III Peroxidase AtPRX71

Abstract: Pectin is a major cell wall component that plays important roles in plant development and response to environmental stresses. Arabidopsis thaliana plants expressing a fungal polygalacturonase (PG plants) that degrades homogalacturonan (HG), a major pectin component, as well as loss-of-function mutants for QUASIMODO2 (QUA2), encoding a putative pectin methyltransferase important for HG biosynthesis, show accumulation of reactive oxygen species (ROS), reduced growth and almost complete resistance to the fungal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 121 publications
(214 reference statements)
1
12
1
Order By: Relevance
“…It is more likely that SlFERL contributes to the positive regulation of immunity by acting as a scaffold, interacting with microbial signatures and pattern recognition receptors, similar to the function of FER and some other malectin-receptor-like kinases in Arabidopsis. Notably, Lorrai et al (2021) previously reported that Arabidopsis fer-4 mutants were more resistant to B. cinerea, while the present study revealed that Slferl mutants were more sensitive to B. cinerea. It has been demonstrated that homozygous Arabidopsis fer mutants were resistant to Golovinomyces (syn.…”
Section: Discussioncontrasting
confidence: 44%
“…It is more likely that SlFERL contributes to the positive regulation of immunity by acting as a scaffold, interacting with microbial signatures and pattern recognition receptors, similar to the function of FER and some other malectin-receptor-like kinases in Arabidopsis. Notably, Lorrai et al (2021) previously reported that Arabidopsis fer-4 mutants were more resistant to B. cinerea, while the present study revealed that Slferl mutants were more sensitive to B. cinerea. It has been demonstrated that homozygous Arabidopsis fer mutants were resistant to Golovinomyces (syn.…”
Section: Discussioncontrasting
confidence: 44%
“…For example, Arabidopsis reduced wall acetylation 2 mutants, that have reduced pectin acetylation, are more resistant to Botrytis cinerea ( Manabe et al, 2011) . The alteration of HG has also been shown to enhance resistance to B. cinerea ( Lorrai et al, 2021 ). Arabidopsis plants overexpressing PMEI-1 and PMEI-2 show enhanced resistance to the phytopathogens B. cinerea and Pectobacterium carotovorum ( Lionetti et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the water loss and ion leakage were nearly fully suppressed in qua2‐1 esmd1‐1 double mutant but not in mur1 esmd1‐1 double mutants (Figs 6c, S16). Finally, during the examination of mur1 epidermis by means of cryo‐SEM we did not detect any morphological signs indicative of loss of cell adhesion that are otherwise readily visible in cell adhesion mutants (Verger et al ., 2018; Lorrai et al ., 2021; Dataset S3b,c). We therefore conclude that the lack of GDP‐ l ‐fucose had a minor effect on the adhesion of epidermal cells, and loss of epidermal cell adhesion was not the cause of elevated water loss observed in mur1 mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from controlling cell wall porosity (Fleischer et al, 1999), RG-II was demonstrated to form borate-dependent linkages with plasma membrane sphingolipids in cultured Rosa cells (Voxeur & Fry, 2014) and boron deficiency affects membrane integrity (Cakmak et al, 1995;Han et al, 2008). Increased ion (Figs 6a, S16) and chlorophyll leakage (Lorrai et al, 2021) observed in mur1 mutants likely stem from the same causes. It is thus possible that elevated membrane permeability, which otherwise does not affect the steady-state leaf conductance, gains significance under conditions of severe water deficit, contributing to high water loss observed in mur1 mutants.…”
Section: How Do Mur1 Mutants Lose Water?mentioning
confidence: 95%